2013
DOI: 10.7763/ijcea.2013.v4.315
|View full text |Cite
|
Sign up to set email alerts
|

Insights from Crystal Size and Band Gap on the Catalytic Activity of Monoclinic BiVO4

Abstract: Abstract-Monoclinic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
3
20
0
1
Order By: Relevance
“…Among the Raman active modes, the peaks at 158 cm −1 and 523.3 cm −1 are assigned to the E g (147 cm −1 ) and A1g (519 cm −1 ) modes respectively, along with a 645.9 cm −1 (640 cm −1 ) signal, all from TiO 2 anatase 38 . On the other hand, the bands located at 346, 375, and 846 cm −1 closely match with the reference by Thalluri et al for m-BiVO 4 (340,375 and 830.4 cm −1 ) 42 observed the shifts for the m-BiVO 4 at 340, 375 and 830.4 cm −121 .…”
Section: Resultssupporting
confidence: 90%
“…Among the Raman active modes, the peaks at 158 cm −1 and 523.3 cm −1 are assigned to the E g (147 cm −1 ) and A1g (519 cm −1 ) modes respectively, along with a 645.9 cm −1 (640 cm −1 ) signal, all from TiO 2 anatase 38 . On the other hand, the bands located at 346, 375, and 846 cm −1 closely match with the reference by Thalluri et al for m-BiVO 4 (340,375 and 830.4 cm −1 ) 42 observed the shifts for the m-BiVO 4 at 340, 375 and 830.4 cm −121 .…”
Section: Resultssupporting
confidence: 90%
“…S1 (ESI arise from Bi-V vibration, and the peak at 815 cm À1 is attributed to V-O vibration. 31,33,34 Raman spectrum of the product is in good agreement with the crystal structure of Zn 3 (VO 4 ) 2 /BiVO 4 . Fig.…”
Section: Resultssupporting
confidence: 73%
“…All these Raman band assignments for the present materials correspond well with the literature reports of similar materials. [70][71][72][73][74][75] It has been observed that there is a blue shi in the most intense peak from 825.50 cm À1 to 829.54 cm À1 in materials from SBM0 to SBM3 then red shiing is observed in SBM5 to SBM7. The change of vibrational frequency of V-O can be explained in terms of metal-oxygen bond length and strength.…”
Section: Resultsmentioning
confidence: 98%
“…The modes at 213.23 cm À1 and 126.58 cm À1 are assigned as rotational and translational modes respectively. [70][71][72][73][74][75] The weak bands at 867.50 cm À1 and 374.70 cm À1 are assigned to the n s (MoO 4 ) and d (MoO 4 ) respectively. The band corresponds to the n as (MoO 4 ) might be covered with 825.50 cm À1 peak.…”
Section: Resultsmentioning
confidence: 99%